Comparison of caries removal using Carisolv or a conventional slow speed rotary instrument on a group of children aged 4-14 years in private specialized clinic in Baghdad - Nidhal Ali; Abduloma Ali; Istabraq Baker (University Library System, University of Pittsburgh, 2023)
Abstract Carisolv is the only NaOCl-based chemical-mechanical caries removal product that is currently available on the market with a pH 11. Participants in the study who had primary caries lesions on their teeth were divided into two groups. The experimental group received chemical-mechanical treatment with Carisolv® gel (N=54) whereas the control group received traditional treatment model- by drilling and excavation (N=47). Children who were participating in the study had at least two primary caries lesions in the same group of teeth and were being treated by a pediatric dentist at a specialty dental clinic. Children with two or more identical caries lesions in the same set of teeth took part in this study. Using Carisolv® gel on one of the selected teeth (the experimental tooth), while drilling and excavating the other tooth as usual, both the experimental and control teeth were placed on the left side of the jaw. It was successful in getting the parents of the children to agree to have them participate in the study. Using Carisolv® gel, we conducted a clinical comparison of the traditional and chemical-mechanical approaches in this study. The aim of this research was to compare a chemical-mechanical approach of caries removal with rotary instruments for children's deciduous and permanent teeth using Carisolv® gel and determine whether anesthesia is required.